Knowledge-based genetic algorithm for multidimensional data clustering - Purnomo, Muhammad Ridwan Andi; Saleh, Chairul; Lagaida, Reny Lituhayu; Hassan, Azmi (Trans Tech Publications Ltd., Switzerland, 2014)
In this paper, a new approach of genetic algorithm called knowledge-based Genetic Algorithm (KBGA-Clustering) is proposed for multidimensional data clustering. Basically, this method adopts knowledge of what called as appropriate cluster centre for a fixed number of kcluster. The chromosome which has inappropriate genes will be penalised with maximum value to prohibit it in the next generation. The experimental result is also provided for KBGA-Clustering and Genetic Algorithm-Clustering (GA-Clustering) to present the performance. Based on the observation, KBGA-Clustering presents better performance and more optimum solution compared to conventional GA-Clustering.